Second-Order Neutral Differential Equations with Distributed Deviating Arguments: Oscillatory Behavior - Asma Al-Jaser; Belgees Qaraad; Omar Bazighifan; Loredana Florentina Iambor (Mathematics, 2023)
In this paper, new criteria for a class oscillation of second-order delay differential equations with distributed deviating arguments were established. Our method mainly depends on making sharper estimates for the non-oscillatory solutions of the studied equation. By using the Ricati technique and comparison theorems that compare the studied equations with first-order delay differential equations, we obtained new and less restrictive conditions that ensure the oscillation of all solutions of the studied equation. Further, we give an illustrative example.